2018
DOI: 10.1177/0095327x18789074
|View full text |Cite
|
Sign up to set email alerts
|

The Curious Relationship Between Military Service and Entrepreneurial Intentions in Israel

Abstract: Our research, based on a sample of 500 veterans currently studying at Israeli colleges and universities, suggests that certain aspects of military service are associated with greater entrepreneurial intentions. Specifically, the desire to engage in entrepreneurship is higher among veterans with command experience than veterans without. Similarly, veterans of technological units generally express greater entrepreneurial interest than veterans of combat units. A comparison of commissioned and noncommissioned off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Particular skills and experiences also affect entrepreneurship. Polin and Ehrman (2018) studied 500 veterans enrolled at Israeli universities and found that those with command experience were more willing to engage in entrepreneurship. Moreover, veterans from technological units usually showed greater interest in entrepreneurship than those from combat units.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Particular skills and experiences also affect entrepreneurship. Polin and Ehrman (2018) studied 500 veterans enrolled at Israeli universities and found that those with command experience were more willing to engage in entrepreneurship. Moreover, veterans from technological units usually showed greater interest in entrepreneurship than those from combat units.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…This begs the question of the applicability of the concept of workplace militarization in other contexts wherever relevant, particularly in countries that still practice conscription (e.g., Israel, Turkey) or experience legacies of military rule (e.g., Japan). In Israel, for instance, it is well known that military experience cultivates human, social, and cultural capital that is exported to and highly appreciated in the work sphere, especially in the hi‐tech sector, a deeply masculine environment (Honig et al., 2006; Polin & Ehrman, 2020; Swed & Butler, 2015). Yet whether and how the authority relations and organizational culture are militarized is unclear.…”
Section: Discussionmentioning
confidence: 99%